Vitamin D status in children with a psychiatric diagnosis, autism spectrum disorders, or internalizing disorders - Muskens, Jet; Klip, Helen; Zinkstok, Janneke R.; van Dongen-Boomsma, Martine; Staal, Wouter G. (Frontiers in Psychiatry, 2022)
Background and Objective Multiple studies suggest that children with Autism Spectrum Disorders (ASD) have significantly lower vitamin D3 levels than typically developing children. However, whether vitamin D3 deficiency is more common in children with ASD than in children with other psychiatric disorders remains unclear. This study was conducted to explore the prevalence of vitamin D3 in children with a psychiatric diagnosis including children with ASD or with internalizing disorders (mood and anxiety disorders). In addition, this study investigated the potential associations between vitamin D3 and Body Mass Index (BMI). Methods Clinical data, including BMI and vitamin D3 levels, of 93 children (6-18y; n=47; 51% female) with ASD (n=58) and internalizing disorders (n=37) were retrospectively analysed. Results In the overall sample, the prevalence of vitamin D3 deficiency (<50nmol/l) was 77.4%. Additionally, 75.9% of the children with ASD and 79.5% with internalizing disorders had vitamin D3 deficiency. BMI was inversely related to vitamin D3 in the total group (p=0.016).The multiple regression model for the total group significantly predicted vitamin D3 (p=0.022). Age contributed significantly to the prediction. Stratified for sex and primary diagnosis, multiple regression models showed that for boys with ASD, higher BMI levels were associated with lower vitamin D3 levels (p=0.031); in boys with internalizing disorders and in girls, no relation was found between BMI and vitamin D3 levels. Conclusion In this this cross-sectional, explorative study high rates of vitamin D3 deficiency in children with different psychiatric disorders were found. The results showed an inverse relation between BMI and vitamin D3 levels in the total group. Vitamin D3 deficiency was particularly common in boys with ASD and obesity. Lifestyle factors may contribute to the association between high BMI and low vitamin D3 levels in boys with ASD. Vitamin D3 deficiency is common in patients with psychiatric disorders and it is highly recommended to increase clinicians’ awareness of this common and remediable risk factor.